Automatic speed limit digital speedometer with speed alarm - Ahmad, Anita (Universiti Teknologi Malaysia, 2012)
Digital is certainly a unique system. It gives the same function as the analog system which has been widely used throughout our life and the innovation of digital appliances has given great impact in our work system. Therefore in this project, a model of an Adjustable Speed Limit Digital Speedometer with Speed Alarm is developed in the laboratory using a PIC microcontroller which will be equipped with a 12-buttons keypad, a two dual digits 7-segment display and also a buzzer. A custom made programming was developed using assembly language for the PIC microcontroller which will be the key of the whole project. In the end of the project, the built model of an Adjustable Speed Limit Digital Speedometer with Speed Alarm will able to display the actual running speed of the vehicle in km/h reading and also the desired speed limit entered by the user in digital mode while the secondary purpose is to have an adjustable speed limit controller as an input for the setting of the speed limit together with a speed alarm that buzzes continuously when the speed limit being set is exceeded by the current running vehicle speed.